RESPONS PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PRE NURSERY AKIBAT PEMBERIAN PUPUK MELALUI DAUN - Edy Usman; Meriyanto Meriyanto; Haris Haris (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2014)
The study aimed to assess the aims of palm oil seeds in the growth response due to pre nursery fertilizer through the leaves. The research was conducted by using a randomized block design experiment, which consists of six treatments were repeated four times. Leaf manure treatment under study consists of: Urea (P1), Gandasil D (P2), Bayfolan (P3), Grow More (P4), NPK Blue (P5), and NPK Yellow (P6). Each treatment consisted of 10 plants that required as many as 240 plant. Parameters observed that plant height, number of midrib, girth and leaf area of plants. The results showed that the application of fertilizer through the leaves did not affect significantly to the growth of palm oil seedlings in pre nursey. In the tabulation of NPK yellow produce better relative growth than other treatments that produce number midrib as 5.25, 5.45 cm of girth and 540.33 cm2 leaf area.